SINTESIS DAN KARAKTERISASI MEMBRAN BIONANOKOMPOSIT SELULOSA BAKTERI-Ag SEBAGAI MEMBRAN ANTIBAKTERI - Dwi Cahyaningsih; Andi Dahliaty; Amilia Linggawati (Jurnal Online Mahasiswa (JOM) Bidang Matematika dan Ilmu Pengetahuan Alam, 2015)
Bacterial cellulose is a potential biopolymer that can be used in the medical field as an antibacterial membrane. Antibacterial membrane was synthesized from bacterial cellulose that was composited with silver nanoparticle that has antibacterial activity. Silver nanoparticles were impregnated into bacterial cellulose membrane to produce bacterial cellulose-Ag bionanocomposite membrane. Synthesis of silver nanoparticles was performed using reduction method with various concentrations of AgNO3 as precursor (0.5 mM, 1 mM, 1.5 mM) and sodium citrate as reducing and stabilizing agent. Bacterial cellulose-Ag bionanocomposite membrane was characterized by Scanning Electron Microscopy-Energy Dispersive X-Ray Spectroscopy (SEM-EDX). The results of SEM-EDX characterization showed that bacterial cellulose-Ag bionanocomposite membrane with AgNO3 0.5 mM has smallest size of silver nanoparticles (30-60 nm) and distributed homogeneously in the bacterial cellulose membrane. Antibacterial test against Staphylococcus aureus and Escherichia coli was carried out by the agar diffusion and turbidimetry method. Bacterial cellulose-Ag bionanocomposite membrane did not show antibacterial activity in the agar diffusion method. In turbidimetry method, bacterial cellulose-Ag bionanocomposite membrane with AgNO3 0.5 mM showed antibacterial activity against Staphylococcus aureus and Escherichia coli. It was able to decrease Optical Density of Staphylococcus aureus (26,69%) and Escherichia coli (22,91%) compared to controls.